The Algorithmic Lifeline: Will AI Solve the Organ Shortage Crisis? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The global organ shortage is a profound public health crisis, with over 100,000 people in the United States alone awaiting a life-saving transplant ^1. This ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care